1999
DOI: 10.1007/s004420050840
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of an arbuscular mycorrhizal fungus on aphid life history traits

Abstract: Two generations of two aphid species (Myzus ascalonicus and M. persicae) were reared on Plantago lanceolata plants, with and without root colonization by the arbuscular mycorrhizal fungus, Glomus intraradices. Life history traits of the aphids measured were nymphal development time, teneral adult weight, growth rate, total fecundity, adult longevity and duration of post-reproductive life. For both aphids in both generations, mycorrhizal colonization increased aphid weight and fecundity, while other traits were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 28 publications
4
74
2
4
Order By: Relevance
“…Aphids had the lowest per capita growth rates and individual masses on plants under medium AMF availability, yet had the highest per capita growth rates and masses on plants under high AMF availability (Figure 2). Thus, we found within a single study the range of aphid responses to AMF from the literature, from positive to negative (Pacovsky et al, 1985;Gange and West, 1994;Gange et al, 1999Gange et al, , 2002Gehring and Whitham, 2002;Wurst et al, 2004;Hempel et al, 2009;Koricheva et al, 2009;Abdelkarim et al, 2011;Babikova et al, 2014a;Colella et al, 2014;Grabmaier et al, 2014;Williams et al, 2014;Bennett et al, 2016;Simon et al, 2017;Tomczak and Müller, 2017). Our findings suggest that some of the previously found variation in aphid responses may result from differences in AMF inoculum availability among studies.…”
Section: Amf Abundance Alters Specialist Herbivore Performance and Sumentioning
confidence: 51%
See 1 more Smart Citation
“…Aphids had the lowest per capita growth rates and individual masses on plants under medium AMF availability, yet had the highest per capita growth rates and masses on plants under high AMF availability (Figure 2). Thus, we found within a single study the range of aphid responses to AMF from the literature, from positive to negative (Pacovsky et al, 1985;Gange and West, 1994;Gange et al, 1999Gange et al, , 2002Gehring and Whitham, 2002;Wurst et al, 2004;Hempel et al, 2009;Koricheva et al, 2009;Abdelkarim et al, 2011;Babikova et al, 2014a;Colella et al, 2014;Grabmaier et al, 2014;Williams et al, 2014;Bennett et al, 2016;Simon et al, 2017;Tomczak and Müller, 2017). Our findings suggest that some of the previously found variation in aphid responses may result from differences in AMF inoculum availability among studies.…”
Section: Amf Abundance Alters Specialist Herbivore Performance and Sumentioning
confidence: 51%
“…For instance, aphids generally benefit from AMF colonization of their host plants; aphids are more attracted to plants colonized by AMF and have greater body masses, growth rates, and fecundity on host plants colonized by AMF (Gange and West, 1994;Gange et al, 1999Gange et al, , 2002Koricheva et al, 2009;Babikova et al, 2014a,b;Simon et al, 2017). However, aphids have also been found to not respond to AMF colonization of their host plants (Pacovsky et al, 1985;Wurst et al, 2004;Colella et al, 2014;Grabmaier et al, 2014;Williams et al, 2014;Bennett et al, 2016) or to have reduced population growth on plants colonized by AMF (Gehring and Whitham, 2002;Hempel et al, 2009;Abdelkarim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that reproductive traits of aboveground herbivorous arthropods can be positively or negatively affected by belowground arbuscular mycorrhizal fungi (Gange et al 1999;Goverde et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gange et al (1999) reported that the fecundity of two species of aphids (Myzus persicae and M. ascalonicus) was enhanced when the aphids fed on mycorrhiza-infected Plantago. Likewise, spider mites (T. urticae) fed on mycorrhiza-infected plants showed increased egg production (Hoffmann et al 2009) although this pattern was in contrast to the findings Koricheva et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…A cursory examination of the literature provides support for these predictions. In all of the annual species examined-Plantago lanceolata (Gange et al 1999(Gange et al , 2002b, soybean (Borowicz 1997), and Abutilon theophrasti (Sanders et al 1993)-herbivore fitness increased on host plants associated with mycorrhizal fungi as predicted by the nutritional hypotheses. However, additional studies with two of these species-Plantago lanceolata (Gange and West 1994) and soybean (Rabin and Pacovsky 1985)-demonstrated a decline in herbivore fitness on host plants associated with mycorrhizal fungi, suggesting a need for further study.…”
Section: Plant Successional Statusmentioning
confidence: 96%